2000
DOI: 10.1177/036354650002800501
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Posterior Capsule Tightness and Motion Loss in Patients with Shoulder Impingement

Abstract: The relationship between posterior capsule tightness and dysfunction has long been recognized clinically but has not been biometrically quantified. The purpose of this study was to quantify changes in range of motion and posterior capsule tightness in patients with dominant or nondominant shoulder impingement. Measurements of posterior capsule tightness and external and internal rotation range of motion were made in 31 patients with shoulder impingement and in 33 controls without shoulder abnormality. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
197
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(209 citation statements)
references
References 27 publications
10
197
1
1
Order By: Relevance
“…A current prospective study could not show any associations between GIRD and shoulder injury [16] and according to Freehill et al [11] there is no consensus regarding what amount of GIRD is the threshold for an increased risk of injury. Many authors have concluded that a mean GIRD range of 10-15°in asymptomatic overhead athletes [12,14,51,52] and a mean range of 19-25°in symptomatic overhead athletes [12,29,30]. Almeida et al [10] reported a significant extension of the GIRD and ERG as well an increase in ER and a decrease in IR ROM in the TS joint of the athletes with regional pain in comparison to the ones without symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A current prospective study could not show any associations between GIRD and shoulder injury [16] and according to Freehill et al [11] there is no consensus regarding what amount of GIRD is the threshold for an increased risk of injury. Many authors have concluded that a mean GIRD range of 10-15°in asymptomatic overhead athletes [12,14,51,52] and a mean range of 19-25°in symptomatic overhead athletes [12,29,30]. Almeida et al [10] reported a significant extension of the GIRD and ERG as well an increase in ER and a decrease in IR ROM in the TS joint of the athletes with regional pain in comparison to the ones without symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated risk factors for shoulder injuries among overhead sport athletes, especially on glenohumeral ROM, strength and scapular dyskinesis [9,10,[14][15][16][25][26][27][28]. There is evidence for the presence of a glenohumeral internal rotation deficit (GIRD) as a primary risk factor for shoulder injuries and damages [12,29,30]. Regardless of which mechanism of pathology, there is evidence for the development of internal posterosuperior glenohumeral impingement syndromes, superior labrum anterior to posterior lesions (SLAP) and anterior instability as a direct result of microtraumatic lesions caused by repetitive throwing [6,15,19,31].…”
Section: Introductionmentioning
confidence: 99%
“…Decrease in glenohumeral internal rotation range has been associated with shoulder impingement in overhead athletes (Borich et al, 2006;Harryman et al, 1990;Tyler et al, 2000) and with impingement symptoms (Myers et al, 2006). This may be attributed to adaptation in the posterior capsule or changes in posterior shoulder contractile tissues (Burkhart et al, 2003;Laudner et al, 2006).…”
Section: Glenohumeral Kinematic Factorsmentioning
confidence: 99%
“…Such mobility impairments cause muscle imbalance and faulty movement patterns. For instance, a fixed kyphotic posture or tight posterior shoulder capsule will need to be mobilized in order for the patient to gain proper control of the scapulo-thoracic articulation (Godges et al, 2003;Tyler et al, 2000;Young et al, 1996). For this reason T4-8 extension mobility exercises such as the upper back cat or foam roll stretches are invaluable.…”
Section: Article In Pressmentioning
confidence: 99%